The role of gut microbiota in intestinal disease: from an oxidative stress perspective - Sun, Yiqi; Wang, Xurui; Li, Lei; Zhong, Chao; Zhang, Yu; Yang, Xiangdong; Li, Mingyue; Yang, Chao (Frontiers in Microbiology, 2024)
Recent studies have indicated that gut microbiota-mediated oxidative stress is significantly associated with intestinal diseases such as colorectal cancer, ulcerative colitis, and Crohn’s disease. The level of reactive oxygen species (ROS) has been reported to increase when the gut microbiota is dysregulated, especially when several gut bacterial metabolites are present. Although healthy gut microbiota plays a vital role in defending against excessive oxidative stress, intestinal disease is significantly influenced by excessive ROS, and this process is controlled by gut microbiota-mediated immunological responses, DNA damage, and intestinal inflammation. In this review, we discuss the relationship between gut microbiota and intestinal disease from an oxidative stress perspective. In addition, we also provide a summary of the most recent therapeutic approaches for preventing or treating intestinal diseases by modifying gut microbiota.